Analysis Autocorrelation Spatial Diarrhea, Typhoid and Leptospirosis on The East Flood Canal, Semarang City: Moran Index Method - Fikri, Elanda; Firmansyah, Yura Witsqa; Ramadhansyah, Muhammad Fadli; Husna, Riyana; Widyantoro, Wahyu; Lewinsca, Maurend Yayank; Arumdani, Intan Sekar; Berlian, Alifia Intan; Novitasari, Karina Laras; Mahendra, Pasha Dwi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Waterborne disease is a disease with water-borne media. The waterborne disease can occur when people come into contact with water that is high in Escherichia coli (a pathogen that causes diarrhea), Salmonella (a pathogen that causes typhoid) and leptospira (a pathogen that causes leptospirosis). This study aims to provide information on the relationship and distribution pattern between canal water consumption and the incidence of waterborne diseases using spatial autocorrelation analysis using the Moran index method. This research is development research with a spatial approach and the Moran index method. From the results of the Moran index autocorrelation, diarrhea has a value of Z(I) = 0.085786 less than Z0.95 = 1.645, which means that there is no spatial autocorrelation, but the distribution pattern is positive so that it is clustered. Typhoid has a value of Z(I) = -0.015495 less than Z0.95 = 1.645, which means that there is no spatial autocorrelation, the distribution pattern is negative and random. While leptospirosis has a value of Z(I) = 0.014872 less than Z0.95 = 1.645, meaning that it has no spatial autocorrelation, the distribution pattern is positive with a clustered form. Efforts are needed for the participation of the Semarang City government in providing access to clean water in several urban areas of Semarang City, assessing parameters and processing water for the East Flood Canal.   Penyakit yang ditularkan melalui air adalah penyakit dengan media yang terbawa air. Penyakit yang ditularkan melalui air dapat terjadi ketika orang bersentuhan dengan air yang tinggi Escherichia coli (patogen penyebab diare), Salmonella (patogen penyebab tifus) dan leptospira (patogen penyebab leptospirosis). Penelitian ini bertujuan untuk memberikan informasi tentang hubungan dan pola distribusi antara konsumsi air saluran dengan kejadian penyakit yang ditularkan melalui air menggunakan analisis autokorelasi spasial menggunakan metode indeks Moran. Penelitian ini merupakan penelitian pengembangan dengan pendekatan spasial dan metode indeks Moran. Dari hasil autokorelasi indeks Moran, diare memiliki nilai Z(I) = 0085786 kurang dari Z0,95 = 1,645 yang artinya tidak terdapat autokorelasi spasial tetapi pola distribusinya positif sehingga mengelompok. Tifus memiliki nilai Z(I) = -0,015495 kurang dari Z0,95 = 1,645 yang berarti tidak terdapat autokorelasi spasial, pola sebarannya negatif dan acak. Sedangkan leptospirosis memiliki nilai Z(I) = 0,014872 kurang dari Z0,95 = 1,645 artinya tidak memiliki autokorelasi spasial, pola sebarannya positif dengan bentuk mengelompok. Diperlukan upaya peran serta Pemerintah Kota Semarang dalam penyediaan akses air bersih di beberapa wilayah perkotaan Kota Semarang, pengkajian parameter dan pengolahan air untuk Kanal Banjir Timur.